Ammonium fluxes into plant roots: Energetics, kinetics and regulation - Glass, Anthony D. M.; Erner, Yair; Kronzucker, Herbert J.; Schjoerring, Jan K.; Siddiqi, M. Yaeesh; Wang, M.-Yuan (Wiley, 1997)
Ammonium uptake across the plasma membranes of seedling roots of intact rice plants is thermodynamically active at low external concentrations, and consequently, electrogenic uniport is an unlikely mechanism for influx. At higher NH4+ concentrations uptake is passive and electrogenic uniport is a possibility. While passive permeation of NH3 is also possible at high external [NH4+], influx measurements at 10 mM NH4+ demonstrated a pH dependence which was inconsistent with significant NH3 permeation. Kinetic studies using 13NH4+ established that influx at low external [H4+] occurred via high affinity transport systems (HATS) in rice and spruce, while at higher [NH4+], influx was mediated by low affinity transport systems (LATS), that showed linear concentration dependence. Ammonium influx via the HATS was shown to be up‐regulated or down‐regulated in response to changes of N status, whereas influx in the LATS was insensitive to N status. The identity or identities of the regulatory signals responsible for controlling influx are discussed.